2018
DOI: 10.2147/idr.s155099
|View full text |Cite
|
Sign up to set email alerts
|

Timing of antibiotic administration and lactate measurement in septic shock patients: a comparison between hospital wards and the emergency department

Abstract: BackgroundThe timing of intravenous antibiotic administration and lactate measurement is associated with survival of septic shock patients. Septic shock patients were admitted to the medical intensive care unit (MICU) from 2 major sources: hospital ward and emergency department (ED). This study aimed to compare the timing of antibiotic administration and lactate measurement between hospital wards and the ED.Patients and methodsMedical data were collected from adult patients admitted to the MICU with septic sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 26 publications
2
5
0
Order By: Relevance
“…In this regard, it should be noted that in our study, when doing a subgroup analysis, we did not find significant differences in mortality with the administration of antimicrobials within 1 h or within 3 h of admission to the ED in patients with septic shock, in contrast to emerging literature that suggests a greater benefit in this population [21,22,26]. These findings are similar to the results of a recent small observational study that included 150 septic shock patients admitted to the medical intensive care unit (MICU) with an in-hospital mortality rate of 49.3%; this study did not show an association between timing of antibiotic administration and mortality [31]. All this would suggest a more prudent-albeit critical-approach to the consideration of the timely and adequate initiation of antimicrobials, in which the initial resuscitation measures and the determination of the focus of infection would be critical.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…In this regard, it should be noted that in our study, when doing a subgroup analysis, we did not find significant differences in mortality with the administration of antimicrobials within 1 h or within 3 h of admission to the ED in patients with septic shock, in contrast to emerging literature that suggests a greater benefit in this population [21,22,26]. These findings are similar to the results of a recent small observational study that included 150 septic shock patients admitted to the medical intensive care unit (MICU) with an in-hospital mortality rate of 49.3%; this study did not show an association between timing of antibiotic administration and mortality [31]. All this would suggest a more prudent-albeit critical-approach to the consideration of the timely and adequate initiation of antimicrobials, in which the initial resuscitation measures and the determination of the focus of infection would be critical.…”
Section: Discussionsupporting
confidence: 85%
“…It is necessary to highlight the restriction regarding the sample size, for which it is not possible to rule out a beneficial effect, although it is important to note that our sample size is one of the largest collected prospectively in a study that shows no association between early administration of antimicrobials and mortality in patients with sepsis [7,[28][29][30][31][32]. Also, the problem of residual confounding-despite the use of the propensity score and adjustment for covariates-cannot be eliminated.…”
Section: Limitationsmentioning
confidence: 99%
“… 21 The timing of antibiotic administration was not associated with in-hospital mortality, similar to our previous report. 15 Although this study was not designed to evaluate the effect of the timing of antibiotic administration, our results supported the position statement of the Infectious Disease Society of America against a fixed timing of antibiotic administration with inappropriate use. 22 …”
Section: Discussionsupporting
confidence: 76%
“…These results were related to our most common source of infection being pneumonia, as in our previous sepsis studies. 14 , 15 Concordant with the source of infection, the respiratory system is the most common site of organ dysfunction in sepsis. A Spanish study reported that the highest incidence of organ failure in sepsis was respiratory failure, accounting for 74.9%.…”
Section: Discussionmentioning
confidence: 99%
“…8,106,107 Apart from the underdiagnosis, 108 other factors are involved in the implementation of the early administration of antibiotics. 10,[109][110][111] In a previous report, patients receiving pre-hospital emergency care and transferred to the emergency department received antibiotics earlier than patients transferred to medical wards. 109 High-quality training programs and improved interprofessional communication 10,100,[112][113][114] are associated with timely empirical antibiotic prescription prior to ICU admission.…”
Section: Early Administration Of Broad-spectrum Antibiotics Ideally In the First Hour Of Diagnosismentioning
confidence: 95%